Oxidative stress-mediated HMGB1 biology - Yu, Yan; Tang, Daolin; Kang, Rui (Frontiers in Physiology, 2015)
High mobility group box 1 (HMGB1) is a widely-expressed and highly-abundant protein that acts as an extracellular signal upon active secretion by immune cells or passive release by dead, dying, and injured cells. Both intracellular and extracellular HMGB1 play pivotal roles in regulation of the cellular response to stress. Targeting the translocation, release, and activity of HMGB1 can limit inflammation and reduce tissue damage during infection and sterile inflammation. Although the mechanisms contributing to HMGB1 biology are still under investigation, it appears that oxidative stress is a central regulator of HMGB1’s translocation, release, and activity in inflammation and cell death (e.g., necrosis, apoptosis, autophagic cell death, pyroptosis, and NETosis). Thus, targeting HMGB1 with antioxidant compounds may be an attractive therapeutic strategy for inflammation-associated diseases such as sepsis, ischemia and reperfusion injury, arthritis, diabetes, and cancer.